Cell interactions in the immune response in vitro. IV. Comparison of the effects of antigen-specific and allogeneic thymus-derived cell factors. - Feldmann, M; Basten, A (1972)
The role of soluble factors in cell collaboration was investigated by means of a tissue culture system in which populations of T and B cells were either incubated together or separated from each other by cell impermeable membranes. Histoincompatible T cells were found to augment antibody responses to both thymus-dependent and thymus-independent antigens, whether they were in contact with B cells or not. The properties of the factor released by the T cells in the allogeneic mixture were compared with those of the previously reported antigen-specific mediator found in syngeneic collaborative antibody responses. Unlike the latter, the factor made in allogeneic responses failed to display any degree of antigen specificity either in its induction or in its action, enhancing responses to all the antigens present in the cultures to a similar degree. It was of lower molecular weight than the antigen-specific factor, because it could pass through dialysis membranes as well as nuclepore membranes, whereas the antigen-specific factor could only penetrate nuclepore membranes. Furthermore, the factor made in allogeneic reactions had a different site of action. It acted directly on B lymphocytes, whereas the antigen-specific component acts through macrophages. Although antigen in the presence of the allogeneic factor did not initiate antibody production, it augmented responses once they had been induced by a matrix of antigenic determinants, either mediated by the antigen-specific factor or directly by a thymus-independent antigen. It was therefore considered to act at a later stage of the antibody response, probably as a nonspecific stimulator of immune B cell proliferation. Observations that the effect on the allogeneic factor are more pronounced 2 days after the beginning of the response are in keeping with this interpretation.